Heterogeneity in Apoptotic Responses of Microvascular Endothelial Cells to Oxidative Stress - Grinnell, Katie (2012)
Oxidative stress contributes to disease and can alter endothelial cell (EC) function. EC from different vascular beds are heterogeneous in structure and function, thus we assessed the apoptotic responses of EC from lung and heart to oxidative stress. Since protein kinase Cδ (PKCδ) is activated by oxidative stress and is an important modulator of apoptosis, experiments assessed the level of apoptosis in fixed lung and heart sections of PKCδ wild-type (PKCδ(+/+)) and null (PKCδ(−/−)) mice housed under normoxia (21% O(2)) or hyperoxia (~95% O(2)). We noted a significantly greater number of TUNEL-positive cells in lungs of hyperoxic PKCδ(+/+) mice, compared to matched hearts or normoxic organs. We found that 33% of apoptotic cells identified in hyperoxic lungs of PKCδ(+/+) mice were EC, compared to 7% EC in hyperoxic hearts. We further noted that EC apoptosis was significantly reduced in lungs of PKCδ(−/−) hyperoxic mice, compared to lungs of PKCδ(+/+) hyperoxic mice. In vitro, both hyperoxia and H(2)O(2) promoted apoptosis in EC isolated from microvasculature of lung (LMVEC), but not from the heart (HMVEC). H(2)O(2) treatment significantly increased p38 activity in LMVEC, but not in HMVEC. Inhibition of p38 attenuated H(2)O(2)-induced LMVEC apoptosis. Baseline expression of total PKCδ protein, as well as the caspase-mediated, catalytically active PKCδ cleavage fragment, was higher in LMVEC, compared to HMVEC. PKCδ inhibition significantly attenuated H(2)O(2)-induced LMVEC p38 activation.. Conversely, overexpression of wild-type PKCδ or the catalytically-active PKCδ cleavage product greatly increased H(2)O(2)-induced HMVEC caspase and p38 activation. We propose that enhanced susceptibility of lung EC to oxidant-induced apoptosis is due to increased PKCδ→p38 signaling, and we describe a PKCδ-centric pathway which dictates the differential response of EC from distinct vascular beds to oxidative stress.